Perancangan Sistem Informasi Penjualan Seragam Sekolah Dasar Berbasis Mobile dengan Menggunakan Metode Prototype - Alda, Muhamad; Hidayat, Riyan; Surbakti, Gita Syahfitri Wulandari; Azmi Pohan, Wulan; Tarigan, Tasya Ika Saylani (Journal of Information System Research (JOSH), 2026)
Advances in information and communication technology have driven digital transformation across various sectors, including education and business, making the use of technology crucial for data processing and sales. Information systems are capable of integrating people, data, processes, and technology to improve efficiency and support decision-making. In the context of education, the use of technology for sales and data processing is important for increasing effectiveness and service quality. However, in the education sector, the sale of elementary school goods is still largely done manually, which can lead to problems such as data inconsistencies, delayed reports, and decreased efficiency. Therefore, an information system is needed that can manage sales transactions and data in an integrated and automated manner. Various previous studies have shown that implementing a digital sales information system can improve data processing effectiveness, minimize recording errors, and support managerial decision-making. As the use of mobile devices increases, the development of mobile-based information systems becomes a relevant solution because it offers ease of access, flexibility of use, and improved customer service quality. In addition, the prototyping method has proven effective in system development because it directly involves users, resulting in a system that is more aligned with user needs. Based on these problems and previous research findings, this study aims to design a Mobile-Based Elementary School Uniform Sales Information System using the prototyping method. This method allows for direct user involvement in the design process, thus creating a system design that is more aligned with user needs. The research results include a system design that encompasses process modeling using the Unified Modeling Language (UML) and the design of the mobile application's user interface. This system design is expected to serve as a reference in the development of an integrated mobile-based school information system and improve efficiency in data processing and sales.